The Contribution of Eurocentric Literature to the Emergence of African Post Colonial Literature - Houria, Mihoubi (My University, 2015)
Abstract This research paper is principally intended to comprehensively examine the contribution of Eurocentric literature to the emergence of African Post colonial Literature. Most Western critics had a firm belief that African literature was a reaction to the distorted image of Africa as portrayed in the Western Eurocentric literature. The present article thoroughly discusses the African reaction to the Eurocentric portrayal of Africa and the Africans which had often tended to portray all that is African in an extremely negative way to the Western reader. The research focuses on Algerian literature as a case study.
Keywords: Keywords: African literatture, European literature, Euro centrism, Afro centrism, colonialism. Introduction